1999
DOI: 10.1089/10430349950017194
|View full text |Cite
|
Sign up to set email alerts
|

Partial Functional Correction of Xeroderma Pigmentosum Group A Cells by Suppressor tRNA

Abstract: Genetic diseases are often caused by nonsense mutations. The resulting defect in protein translation can be restored by expressing suppressor tRNA in the mutant cells. Our goal was to demonstrate both protein restoration and phenotypic correction using these small transgenes. Functional activity of an arginine opal suppressor tRNA in cells expressing a nonsense mutated GFP gene was demonstrated by restored fluorescence. This suppressor tRNA was expressed in xeroderma pigmentosum group A cells, containing a hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 48 publications
(44 reference statements)
0
32
0
Order By: Relevance
“…Approaches that have been considered for treatment of these diseases include aminoglycoside antibiotic induced read-through of the nonsense codon (41) and gene therapy involving suppressor tRNA genes (42,43) or complementation with a wild-type copy of the gene that was mutated, for example, the dystrophin gene for some patients with muscular dystrophy (44). In transgenic mouse model systems expressing a reporter CAToc27 gene (19) in the heart, under control of the ␣-myosin heavy chain gene promoter (45), Leinwand and coworkers have shown that injection of plasmid DNA carrying an ochre suppressor tRNA gene directly to the heart myocardium leads to partial suppression of the ochre mutation in the CAT gene (46).…”
Section: Discussionmentioning
confidence: 99%
“…Approaches that have been considered for treatment of these diseases include aminoglycoside antibiotic induced read-through of the nonsense codon (41) and gene therapy involving suppressor tRNA genes (42,43) or complementation with a wild-type copy of the gene that was mutated, for example, the dystrophin gene for some patients with muscular dystrophy (44). In transgenic mouse model systems expressing a reporter CAToc27 gene (19) in the heart, under control of the ␣-myosin heavy chain gene promoter (45), Leinwand and coworkers have shown that injection of plasmid DNA carrying an ochre suppressor tRNA gene directly to the heart myocardium leads to partial suppression of the ochre mutation in the CAT gene (46).…”
Section: Discussionmentioning
confidence: 99%
“…tRNA suppression and the more recent use of aminoglycoside antibiotics have been suggested as potential gene therapy approaches to restore translation of mRNAs that contain nonsense mutations which cause a large number of human diseases through premature termination of translation (4,38,50).…”
Section: Discussionmentioning
confidence: 99%
“…Since nonsense mutations are associated with an increasing number of human genetic diseases (3), suppressor tRNAs have also been studied as possible therapeutic agents for both ␤°t halassemia and xeroderma pigmentosum (38,50). Even though these reports provided the first promising evidence for a potential clinical use of tRNA-mediated suppression, they did not demonstrate suppression in vivo in mammals.…”
mentioning
confidence: 99%
“…Suppression of nonsense mutations by sup-tRNAs has been demonstrated in Xenopus oocytes 38 and in mammalian cells, 20,22 and was studied later as putative therapeutic tools for diseases like b-thalassaemia, 23 xeroderma pigmentosum 24 and DMD. 15 Nevertheless, formal proof of functional recovery was rarely reported.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies demonstrated efficient nonsense suppression in mammalian models, although the recovery of functional proteins was rarely shown. 15,20,[22][23][24][25] In this work we wish to: (1) evaluate the potential impact of using nonsense suppression in HDGC; (2) determine the number of tRNAs necessary to treat nonsense mutation-carrying HDGC families; and (3) assess the possibility of recovering expression of a functional protein from an allele carrying a nonsense mutation described in HDGC using a sup-tRNA. To our knowledge, this is the first demonstration of functional recovery of a causative gene in cancer by cognate amino acid replacement with sup-tRNAs.…”
Section: Cdh1mentioning
confidence: 99%